Law and Ethics in Medical Practice in Bangladesh: Issues & Impediments (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Medical carelessness and misconduct are prevalent health concerns in Bangladesh. Individuals encounter diverse challenges within the healthcare industry in Bangladesh. Individuals receive services from both government hospitals and private hospitals and clinics, but the quality and adequacy of healthcare services and facilities still need improvement. The paper aims to examine the prevalence and nature of medical negligence and malpractice in Bangladesh, assess existing legal remedies, and identify policy measures to improve accountability and quality of care. This study employs a narrative review of existing literature, including academic publications, policy documents, legal frameworks, and relevant case reports on healthcare delivery and medical misconduct in Bangladesh. The review synthesizes evidence on systemic challenges, patterns of negligence, and the effectiveness of current legal and regulatory mechanisms. The review finds that patients in Bangladesh face significant deficiencies in both public and private healthcare systems, including inadequate service quality, limited accountability, and uneven access to care. Medical negligence and malpractice emerge as persistent issues, driven by weak regulatory enforcement, lack of professional oversight, and insufficient patient protection mechanisms. Existing legal remedies are often underutilized or ineffective due to procedural complexity, low public awareness, and barriers to access. These challenges affect individuals across socioeconomic groups, highlighting systemic weaknesses in healthcare governance. Strengthening regulatory oversight, improving professional accountability, and enhancing patient rights protections are critical to addressing medical negligence in Bangladesh. Reforms should include clearer legal pathways for redress, increased public awareness of patient rights, standardized clinical protocols, and stronger monitoring of healthcare providers. Policy interventions aimed at transparency, training, and institutional accountability are essential to ensure equitable and quality healthcare delivery.J Bangladesh Coll Phys Surg 2026; 44: 127-134